Teacher Collaboration in German Schools: Do Gender and School Type Influence the Frequency of Collaboration Among Teachers? - Mora-Ruano, Julio G.; Gebhardt, Markus; Wittmann, Eveline (Frontiers in Education, 2018)
According to the literature, collaboration among teachers can be regarded as a subject that can positively influence numerous aspects of the school. However, factors influencing the extent to which collaboration takes place have received less attention. For example, gender differences are usually not examined. We carry out a secondary analysis of the representative PISA 2012 German teacher sample to measure the state of teacher collaboration through three different collaboration forms namely instruction-, project- and organization related. Because of the stratification of the German school system in secondary education, variations by school type should be taken into account. We conducted a MANCOVA to investigate the differences and effects that gender and school type of the lower secondary education have on the frequency with which teachers collaborate. Age and experience (in years) were used as covariates. Results show that women collaborate minimally more than men, that the higher the formal education of a school, the less frequently collaboration occurs and that the overall level of collaboration is weak. There is no interaction effect between these two variables. Suggestions for future research as well as implications are presented.